2021
DOI: 10.1111/aogs.14240
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of methicillin‐resistant Staphylococcus aureus at delivery and its clinical impact: An observational, prospective cohort study

Abstract: IntroductionMethicillin‐resistant Staphylococcus aureus (MRSA) infection has a significant clinical impact on both pregnant women and neonates. The aim of this study was to assess accurately the vertical transmission rate of MRSA and its clinical impacts on both pregnant mothers and neonates.Material and methodsWe conducted a prospective observational cohort study of 898 pregnant women who were admitted to our department and 905 neonates from August 2016 to December 2017. MRSA was cultured from nasal and vagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…A Japanese study from 2021 (n=898) concluded that a group of 55 mothers had MRSA colonization and delivered babies, of which 12.7% of neonates had MRSA isolates recovered from them at birth [ 6 ]. From the remainder population of 843 mothers without MRSA colonization, only one baby had an MRSA isolate recovered, thereby indicating that maternal colonization does play a significant role in the neonatal outcome.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A Japanese study from 2021 (n=898) concluded that a group of 55 mothers had MRSA colonization and delivered babies, of which 12.7% of neonates had MRSA isolates recovered from them at birth [ 6 ]. From the remainder population of 843 mothers without MRSA colonization, only one baby had an MRSA isolate recovered, thereby indicating that maternal colonization does play a significant role in the neonatal outcome.…”
Section: Reviewmentioning
confidence: 99%
“…Those in perinatal care are even more likely to be compromised hosts of the bug, in particular premature babies, and those being admitted to the neonatal intensive care unit (NICU); thus, the mother-child relationship in terms of MRSA infections has significant importance in the field of obstetrics [6]. Some risk factors associated with neonatal MRSA infection are low birth weight, early gestational age at birth, indwelling catheters, duration of antibiotic administration, or the number of days on a ventilator [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Colonization with S. aureus in peripartum patients is common and has been associated with invasive infections-such as skin and soft tissue infections, mastitis, pneumonia, and sepsis-as well as vertical transmission, and adverse neonatal outcomes. [7][8][9][10] Moreover, a prolonged course of intravenous antibiotics is often needed for patients with S. aureus bloodstream infections, including through peripherally inserted central lines, which are at increased risk of infectious and thromboembolic complications during pregnancy. 11 S. aureus infections in pregnancy have also been linked to significant healthcare utilization and subsequent economic burden.…”
mentioning
confidence: 99%